EXAMINING ZINC RELEASE FROM PLATELETS AND ITS MODULATION OF CLOT STRUCTURE AND FIBRINOLYSIS - HENDERSON, SARA (My University, 2016)
Zinc (Zn2+) is an abundant metal ion that circulates in the body. Within hemostasis, Zn2+ participates in platelet aggregation, coagulation, and fibrinolysis. At the site of injury, Zn2+ released from activated platelets accelerates coagulation and attenuates fibrinolysis. How Zn2+ regulates these processes on a molecular level has not been extensively examined. We hypothesized that Zn2+ released from platelets binds serine proteases involved in coagulation or fibrinolysis and modulates their proteolytic activity, thus controlling the rate of clot formation and lysis. We show that Zn2+ concentrations released from activated platelets are sufficient to modulate clot formation and fibrinolysis. We show in vitro that Zn2+ binds to fibrinogen with high affinity, accelerates fibrin monomer polymerization, and modifies clot structure. Zn2+ promotes clot stability by increasing fiber diameter, reducing fibrin fiber elasticity, and increases clot porosity. Although it might be predicted that these modifications would enhance clot degradation by enabling greater distribution of lytic enzymes through the more porous fibrin network, we showed the opposite. Thus, we demonstrated that Zn2+ binds to plasminogen activators and plasmin with high affinity and down-regulates their protease activity, which delays lysis. This adds to previous studies that showed that both coagulation and fibrinolysis are regulated by Zn2+ ions. These data support the functional role of Zn2+ in hemostasis.
Keywords: ZINC; COAGULATION; FIBRINOLYSIS; PLATELETS